Confirmed by integrative taxonomy first and unusual occurrence of the exotic shrimp Neocaridina davidi (Caridea: Atyidae) in Brazil - Bochini, Gabriel Lucas; Rios, Aline Dos Santos; Teles, Jeniffer Natalia; Zara, Fernando José [UNESP]; Mantelatto, Fernando Luis (Boletim do Instituto de Pesca, 2024)
A shrimp specimen of the genus Neocaridina Kubo 1938, originally from Asia, was collected for the first time in a natural marine environment in Pernambuco, Brazil. This represents the first record of this genus in the South American continent. Morphological characteristics and mitochondrial and nuclear DNA sequences (COI, 16S, 18S, and H3) of the specimen were compared with other species of Neocaridina, enabling its identification as Neocaridina davidi. Finding this freshwater species native to mainland China in a marine environment was surprising. Based on prior findings in other locations, the most likely hypothesis for this unusual occurrence is that the shrimp may have been released intentionally or unintentionally into the environment by an aquarium hobbyist.
Confirmada pela taxonomia integrativa a primeira e incomum ocorrência do camarão exótico Neocaridina davidi (Caridea: Atyidae) no Brasil
Keywords: Alien species; Aquarism; Decapoda; Ornamental invertebrates; South Atlantic